Research on the Application of Artificial Intelligence in the Field of Public Health —- From the Perspective of the Guarantee Mechanism of Intelligent Drug Rehabilitation - Xiu Chen (Forest Chemicals Review)
The proliferation of drugs is one of the important public health crises facing the world. Despite the rapid development of smart drug rehabilitation in my country, decision-makers still have insufficient understanding of the problems in the construction of smart drug rehabilitation. There are still many problems in the concept of construction and the construction of a guarantee mechanism. This makes the research on the guarantee mechanism of smart drug rehabilitation still arduous. The road is far away. The research of this subject is conducive to building a new pattern of the security mechanism for smart drug rehabilitation in the information age, perfecting the grassroots public health construction system, ensuring the smooth progress of smart drug rehabilitation tasks, summarizing the demonstrative experience formed in practice, and optimizing strategies for smart drug rehabilitation, To meet the actual needs of the development of smart detoxification.